Las estrategias metodológicas y su influencia en la iniciación de la lectura en los niños y niñas del primer año de educación básica de la escuela Eulogio Serrano Armijos de la ciudad de Machala periodo lectivo 2011 - 2012. - Párraga Prado, Karina Angélica (2015)
Reading is one of the more skills considered important for learning in life for all people, is one of the highest functions of the brain and is a guarantee of success in school and in the life of anyone , so it is important determine the influence of methodological strategies in the initiation of reading in children in the first year of primary school Dr. Eulogio Serrano Armijos in the city of Machala academic year 2012 - 2013 .